Procyclicality and the Search for Early Warning Indicators - Shin, Hyun (IMF Working Papers; Working Paper ;, 2013)
This paper compares three types of early warning indicators of financial instability - those based on financial market prices, those based on normalized measures of total credit and those based on liabilities of financial intermediaries. Prices perform well as concurrent indicators of market conditions but are not suitable as early warning indicators. Total credit and liabilities convey similar information and perform better as early warning indicators, but liabilities are more transparent and the decomposition between core and non-core liabilities convey additional useful information.